Faith and the future force - Houser, Jody (Valiant Entertainment LLC, 2018)
Every second will count when acclaimed writer Jody Houser (Mother Panic, Star Wars: Rogue One), explosive artist Stephen Segovia (Ninjak, Action Comics), comics legend Barry Kitson (Fantastic Four), and special surprise guests push Faith into a centuries-spanning fight for existence alongside the greatest heroes of the valiant universe...past, present, and future! Faith "Zephyr" Herbert - former member of Unity, current Harbinger Renegade, and Los Angeles' #1 superhero - is the universe's last, best chance at survival! Centuries from today, a devious artificial intelligence has unleashed a blistering attack on the very foundations of time...one that is the unwriting history from beginning to end! Now, with her options exhausted, Neela Sethi, Timewalker - the self-appointed protector of what is and will be - has returned to the 21st century to recruit Earth's greatest champions of today and tomorrow to oppose this existential threat...and she needs Faith to lead them! But why Faith? And why now? Fly to the farthest edges of the future right here in a death-defying race to save time itself as Faith leads the charge alongside Valiant's greatest heroes...and becomes a new legend for the ages!